2022
DOI: 10.1101/2022.11.09.515902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortico-ocular coupling in the service of episodic memory formation

Abstract: Encoding of visual information is a necessary requirement for most types of episodic memories. In search for a neural signature of memory formation, amplitude modulation of neural activity has been repeatedly shown to correlate with and suggested to be functionally involved in successful memory encoding. We here report a complementary view on why and how brain activity relates to memory, indicating a functional role of cortico-ocular interactions for episodic memory formation. Recording simultaneous magnetoenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…This suggests that low-level control of eye movements was not altered, but simply that our gaze canvases a wider area of the visual field when we naturally listen to a story. This result on gaze variation is consistent with a recent study, which shows that gaze variability (about a fixation cross) during pre-stimulus baseline correlated negatively with alpha power in the EEG 66 . Both alpha power and gaze variability were predictive of subsequent memory of the upcoming visual scene.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that low-level control of eye movements was not altered, but simply that our gaze canvases a wider area of the visual field when we naturally listen to a story. This result on gaze variation is consistent with a recent study, which shows that gaze variability (about a fixation cross) during pre-stimulus baseline correlated negatively with alpha power in the EEG 66 . Both alpha power and gaze variability were predictive of subsequent memory of the upcoming visual scene.…”
Section: Discussionsupporting
confidence: 92%
“…This stimulus information then travels to the hippocampus, where hippocampal theta power increases allow for mnemonic information to be integrated into a coherent memory trace via long‐term potentiation. More recently, alpha oscillations have also been associated with micro‐saccades and gaze toward to‐be‐encoded stimuli indicating that changes in alpha/beta power, especially in the visual cortex, could also be involved in memory formation (Popov & Staudigl, 2023; Staudigl et al, 2017). Therefore, there are theoretical and computational models backed by empirical evidence that indicate changes in theta and alpha/beta oscillations (~4–30 Hz) are involved in associative memory formation.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm compares neural activity during the encoding of trials that are later remembered to those that are forgotten. Studies have demonstrated that oscillatory activity, particularly event-related synchronization of mid-frontal theta (i.e., mid-frontal theta ERS) and desynchronization of parietal alpha (i.e., parietal alpha ERD), contribute to improved memory performance [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%